Hail! Tudors - Steele, Philip, 1948- (Hail! history., 2010)
This entertaining book traces the lives and loves of the extraordinary family of English kings and queens, the Tudors, from the time when Henry VII came to the throne to the death of Elizabeth I. It includes features on that larger-than-life monarch, Henry VIII, and his wives, the Shakespearean theatrical tradition, food and feasting, the destruction and sale of the monasteries, exploration, and trade.